Variation in virulence and aggressiveness among pathotypes of Sclerospora graminicola on pearl millet - V.P. RAO, R.P. THAKUR and (Indian Phytopathology, 2002)
Five pathotypes of S. graminicola, specific to Pennisetum glaucum genotypes, were evaluated for virulence (a qualitative measure of the relative capacity of an isolate to infect a host genotype), aggressiveness (a quantitative measure of the infection causing potential of an isolate, calculated as disease incidence), and virulence index (a quantitative measure of virulence, measured as disease incidence Xlatent period-1) on a set of P. glaucum genotypes in a greenhouse. The pathotypes were selected from a field population of the pathogen through a number of successive asexual generations on specific host genotypes. These were named as pathotype, Path 1 (host NHB 3), Path 2 (BJ 104), Path 3 (MBH 110), Path 4 (852B) and Path 5 (a field population from a mixture of NHB 3 and 7042S). The pathotypes differed significantly in virulence, aggressiveness and virulence index on the host genotypes. Highly significant (P